The Urgency of Implementing Absolute Complaint-Based Criminal Offenses for Domestic Violence in the New Criminal Code: A Study in the Jurisdiction of the Pinrang Police Department - Perdana Herryanto Sultan; Sitti Fausia (Journal of Social Research, 2026)
This study aims to analyze the regulation of absolute complaints for domestic violence crimes (KDRT) in the New Criminal Code and its implementation in the jurisdiction of the Pinrang Police. The research uses empirical juridical methods with a legislative approach, a case approach, and a sociological approach. Data was obtained through interviews with investigators of the Pinrang Police PPA Unit and Pinrang District Court Judges as well as case document studies. It was found that the placement of violence within the scope of marriage as an absolute complaint offense through Article 473 paragraph (6) of the New Criminal Code was followed by a decrease in the number of domestic violence reports, as well as giving rise to new obstacles in the form of pressure on victims to withdraw complaints before the case is completed. This study is one of the initial studies on the work of the provisions of the absolute complaint of domestic violence in the New Criminal Code in the South Sulawesi region.